(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Limited raw materials and energy resources are actual national economy problems which can be solved by the decrease of weight, increase of span and durability of load bearing structures. The largest structural spans were achieved by application of cable structures. The roofs are one of the most widely used in practice type of cable structures. However, increased deformability and necessity of the special methods of stabilizing are significant cable roofs disadvantages. The prestressing of one or several groups of cables is one of the probable methods for stabilizing of cable roofs. According to the recommendations available in the literature, all cables of the roof must be prestressed by the equal forces. But after applying of design vertical load, values of the forces, acting in the cables of the roof, changes within the wide limits. So, using of structural materials will not be rational in this case, taking into account, that the cables cross-sections are constant because the cables cross-sections were determined basing on the maximum axial force, acting in the all cables.Possibility to decrease materials consumption by the changing of prestressing forces for cables of the roof was checked on the example of saddle-shaped cable roof with the rigid support contour and dimensions 60x60 m in the plan. Initial deflections of main suspension and stressing cables of the roof were equal to 7m. Suspension and stressing cables of the net were placed with the step equal to 2.828 m. Steel ropes with modulus of elasticity in 1.5∙105 MPa were considered as a material of suspension and stressing cables of the roof. Suspension and stressing cables were divided into the groups, which are differed by the prestressing forces. Amount of cables groups changes within the limits from 1 to 27. Values of prestressing forces for cables groups change within the limits from 20 to 80% from the cables breaking force. The dependences of material consumption and maximum vertical displacements of cable roof on the amount of cables groups and prestressing forces were determined as second power polynomial equations. It was stated, that division of suspension and stressing cables on the 18 groups enables to decrease cables material consumption by 19.2%. Values of prestressing forces for suspension and stressing cables of the roof were equal to 57 and 80 %, from it load-carrying capacity, correspondingly.